2006
DOI: 10.1136/bjo.2006.094656
|View full text |Cite
|
Sign up to set email alerts
|

Long term results of primary posterior chamber intraocular lens implantation for congenital cataract in the first year of life

Abstract: Intraocular lens implantation in infants less than 1 year of age is generally a safe procedure. The spread of final refractive error was very wide. Final refraction in the unilateral group was significantly more myopic than the bilateral group. Final acuities were often disappointing especially in the unilateral group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 12 publications
3
28
0
3
Order By: Relevance
“…old [2][3][4][5]. It has been reported that a younger age at the time of surgery, has been positively correlated with the development of postoperative complications requiring secondary surgery.…”
Section: Introductionmentioning
confidence: 97%
“…old [2][3][4][5]. It has been reported that a younger age at the time of surgery, has been positively correlated with the development of postoperative complications requiring secondary surgery.…”
Section: Introductionmentioning
confidence: 97%
“…Gouws et al [14] reported on 18 infants undergoing surgery at less than 1 year of age with a mean follow-up of 95 months: best outcomes were in the bilateral group where 50 per cent of eyes achieved 6/18 or better, with a best acuity of 6/9. Acuities were worse in the unilateral group where only 38 per cent achieved 6/60 or better, with a best acuity of 6/24.…”
Section: Clinical Aspects Of Congenital or Paediatric Cataract (A) Comentioning
confidence: 99%
“…Primary IOL implantation has become the treatment of choice in older children, with medium- to longer-term outcome data becoming available,2 3 20 and there is good biocompatibility evidence for IOL material implantation in young eyes 21. Short-term visual rehabilitation following IOL implantation in early childhood is at least comparable with that with contact lens correction of surgical aphakia,5 7 22 23 but there is uncertainty about both the long-term benefits and the risks of primary IOL implantation in children aged under 2 years, with regards to the predictability of refractive outcomes with different power equations, postoperative complication rates and the need for further surgery 7 23 24 25. The Infant Aphakia Treatment Study, currently under way in North America, is investigating outcomes in a defined cohort of infants under 6 months old with unilateral cataract6 following standardised cataract surgery with and without primary IOL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…While primary IOL implantation is being increasingly undertaken in children in the first 2 years of life,3 4 the long-term benefits and the factors associated with positive and negative outcomes are unclear 1 2 5 6 7 8 9…”
mentioning
confidence: 99%